Maternal behaviour in septal rat females - Nováková, V; Sterc, J; Kuchár, S; Mozes, S (Physiological research, 1993)
Dorsal lesions of the septum influenced the maternal behaviour of Wistar and Long-Evans females, as well as of their hybrids, in a different way. The phenomenon of infanticide appeared in Wistar females only, whereas mothering was not impaired in others. However, the mouse-killing activity was not enhanced in Wistar females displaying infanticide. On the contrary, they exhibited xenoparental behaviour. If these females had grown up in a species-typical environment, characterized by enriched social stimulation during their critical developmental period, no impairment of maternal behaviour following dorsal septal lesions occurred. The ablation of the whole septum caused a break-down of maternal behaviour with the appearance of infanticide in all females regardless of their stock origin and their individual life history. The specific role of the septum in the control of maternal behaviour is discussed.
Keywords: Animals; novorozená zvířata; Female; Rats, Wistar; inbrední kmeny potkanů; ženské pohlaví; Animals, Newborn; chování zvířat; Mice; Rats, Inbred Strains; Maternal Behavior; myši; agrese; krysa rodu Rattus; Aggression; Behavior, Animal; mateřské chování; Septum Pellucidum; zvířata; Rats; septum pellucidum; potkani Wistar